Pengelolaan hipertensi dengan pendekatan pelayanan dokter keluarga - Palandeng, Henry M. F. (JURNAL KEDOKTERAN KOMUNITAS DAN TROPIK, 2018)
Hypertension is a condition where blood pressure is permanently above normal. This disease often does not cause symptoms so it is called the silent killer. The prevalence of hypertension in Indonesia at the age of >18 years was 26.5% with the number of patients diagnosed by health workers at 9.4%. About 1% of people with hypertension can experience a crisis hypertension. A holistic approach is needed to determine the risk factors for hypertension. The role of the family is very important in the treatment of hypertension to improve the quality of life. Primary data is obtained through history, physical examination, home visit to assess the condition of the house and family. Results are presented in the form of case reports. In this case, the patient has several risk factors for hypertension. Patients and families have been given education related to hypertension, risk factors, treatment, and recommendations for a healthy lifestyle.